Natural sequence of recovery from child post-traumatic amnesia: A retrospective cohort study. Issue 6 (17th August 2016) - Briggs, Rachel; Birse, Jason; Tate, Robyn; Brookes, Naomi; Epps, Adrienne; Lah, Suncica
Abstract : The aim of this study was to determine the sequence of skills recovery during post-traumatic amnesia (PTA) in children with moderate to severe traumatic brain injuries (TBIs). Setting: Fifty children aged 8 to 15 years consecutively admitted to a children's hospital with TBI and PTA>24 were tested in a retrospective cohort study where the main measure was the Westmead PTA Scale (WPTAS). The group analyses show that orientation to time took longer to recover than orientation to person and place, but not memory, while the individual analyses revealed that when orientation to time was grouped with memory, 94% of children recovered orientation to person and place before orientation to time and memory (examiner and pictures). Correlation coefficients between age and the number of days taken to recover skills were not found to be significant. It was established that, in terms of the natural sequence of skills recovery in children aged 8 to 15 years following moderate to severe TBI, recovery of orientation to time is more closely aligned to memory than to orientation to person and place. It was also established that WPTAS items are developmentally appropriate for children aged 8 to 15 years who have sustained TBI. These findings are clinically important because monitoring recovery from PTA both impacts the rehabilitation offered to individuals during acute care and aids discharge planning.